2012
DOI: 10.1371/journal.pone.0030676
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 Expression Characterizes Regulatory T Cells in Tumor Tissues and Is Associated with Lung Cancer Progression

Abstract: BackgroundT cell immunoglobulin-3 (TIM-3) has been established as a negative regulatory molecule and plays a critical role in immune tolerance. TIM-3 is upregulated in exhausted CD8+ T cells in both chronic infection and tumor. However, the nature of TIM-3+CD4+ T cells in the tumor microenvironment is unclear. This study is to characterize TIM-3 expressing lymphocytes within human lung cancer tissues and establish clinical significance of TIM-3 expression in lung cancer progression.MethodologyA total of 51 hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
294
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(307 citation statements)
references
References 21 publications
11
294
0
2
Order By: Relevance
“…In patients with NSCLC, approximately 60% of CD4 þ FoxP3 þ TILs express Tim-3. Interestingly, these Tim-3 þ Tregs are infrequent in the peripheral blood of patients with NSCLC, and the presence of Tim-3 þ Tregs correlates with the presence of nodal metastases and advanced cancer stage (11). Importantly, the presence of Tim-3 þ Tregs seems to be a common feature across multiple different cancers as Tim-3 þ Tregs have been reported in hepatocellular, ovarian, colon, and cervical carcinomas (20).…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 96%
See 3 more Smart Citations
“…In patients with NSCLC, approximately 60% of CD4 þ FoxP3 þ TILs express Tim-3. Interestingly, these Tim-3 þ Tregs are infrequent in the peripheral blood of patients with NSCLC, and the presence of Tim-3 þ Tregs correlates with the presence of nodal metastases and advanced cancer stage (11). Importantly, the presence of Tim-3 þ Tregs seems to be a common feature across multiple different cancers as Tim-3 þ Tregs have been reported in hepatocellular, ovarian, colon, and cervical carcinomas (20).…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 96%
“…In patients with advanced melanoma, approximately 30% of NY-ESO-1-specific CD8 þ T cells express Tim-3 (10). In patients with non-small cell lung cancer (NSCLC), approximately one third of CD8 þ tumor-infiltrating lymphocytes (TIL) express Tim-3 (11). In patients with follicular B-cell non-Hodgkin lymphoma (FL; ref.…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…It suggested that 2 coinhibitory receptors are correlated with dysfunction of T cells as well as tumor progression. [41][42][43] Collectively, targeting TIM-3 and PD-1 will potentially restore T cell function, which is worthy to be investigated in clinical practice. 44 Two clinical studies regarding dual targeted therapy on advanced malignancies are in development (NCT02817633 and NCT02608268; Table 1).…”
Section: Combination Strategiesmentioning
confidence: 99%